Prevalence of Malnutrition in the Rural Community (TAJ: Journal of Teachers Association, 2018)
This was a cross sectional type of descriptive study which was conducted in four villages of Puthia Upozila of Rajshahi district. A preformed interview schedule was used to collect data from a purposively selected sample of 518 respondents. The study revealed that 42.9% children had 1st degree malnutrition, about 19.5% children had 2nd malnutrition and 1.7% had 3rd degree malnutrition. The mean age of the children was 3.45 ± SD 1.33 years. Out of 518 respondents 74.7% had monthly income of Tk. 5000/- or less and 25.3% respondents had monthly income of Tk. 5001/- and above. The mean monthly was Tk. 5039/- ± SD 3869.36.Undernutrition was more in female children (70.1%) than male children (51.2%). In large family size under nutrition were more (68.4%) in comparison to small family size (61.4%). The study would be helpful in future community survey on nutritional status of under five children and in formulating effective national nutrition health program and facilitating their effective implementation.TAJ 2012; 25: 13-16